The effects of pension information on individuals' economic outcomes: A survey - Stefania Basiglio; Noemi Oggero (Economies, 2020)
This paper provides an overview of a wide array of research investigating the effects of pension information on different individuals' economic outcomes. While many studies show that information provision increases knowledge, the evidence is mixed regarding its effects on behavior. Nevertheless, we draw some conclusions about the impact of pension information on three major economic outcomes, namely, retirement planning, choices pertaining individuals' labor supply, and savings decisions. We also highlight that the lack of knowledge prevalently hits the most vulnerable individuals in the society, such as women. As a consequence, not providing sufficient information could contribute to widening the gender gap in pensions.
Keywords: D14; J26; J16; 330; pension information; retirement; savings; gender gap